Kajian Pemanfaatan Buah Mangsi (Phyllanthus reticulantus poir) sebagai Pewarna alami pada Kain Batik - Titik Irawati (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
The need for natural dyes for environmentally safe batik cloth is the reason for exploring the mangosteen fruit plant. The use of synthetic dyes in batik cloth harms the environment in the form of water and soil pollution around the batik production area. Therefore, there is a need for research studies on natural dyes for batik cloth so that they can provide alternative solutions to these environmental problems. This study aims 1) to determine the characteristics of the mangosteen fruit (Phyllanthus reticulates pair) as a source of natural dyes, 2) to determine the stability of the mangosteen fruit (Phyllanthus reticulates pair), 3) to determine the quality of the fabric at the level of color fastness. This study used a completely randomized design, the first step was to determine the concentration of HCl (1%, 1.5%, 2%) and maceration time (30 minutes and 60 minutes). The second stage is testing the stability of the dye against the influence of pH, temperature, and heating time. The third stage is to test the quality of the fabric by testing the color fastness due to washing and dry rubbing. The data from this study will be analyzed by analysis of variance (ANOVA) and followed by the BNT test (?=0.05%). The results of the FTIR test showed that in the mangosteen fruit extract, there are functional groups that have similarities to the functional groups contained in the basic structure of anthocyanins. 1% HCl (in 95% ethanol) and 60 minutes of maceration time resulted in the highest anthocyanin content (0.411mg/L) and the highest absorbance (0.918), stable at pH 3, temperature 70º C and heating time 30 minutes, application on fabric with the fixation of the average color fastness test to washing 4 (good) and color fastness test to dry rubbing 4 – 5 (very good).